Effect of additional Eucheuma spinosum seaweed flour on feed towards the growth and survival of fish carp (Cyprinus Carpio) - Irmadiati, Irmadiati; Lumbessy, Salnida Yuniarti; Azhar, Fariq (Universitas Malikussaleh, 2021)
The purpose of this research is to analyze the additional flour eucheuma spinosum on feed to the growth and survival of goldfish. Research carried out for 40 days in the Laboratorium basah, Program Studi Budidaya Perairan, Fakultas Pertanian, universitas mataram. The method used is the experimental random complete (RAL) which includes 4 treatments and 3 replacements, so the total of this experiment is 12 units. The treatment that research is the addition of different flour E. Spinosum in feed, consists of: P1: control (without additional flour E. Spinosum), P2: flour E. Spinosum 4 %, P3: flour E. Spinosum 8 %, P4: flour e. Spinosum 12 %. The results of this study indicate that the addition of flour E. spinosum feed has a significant effect on the growth of absolute, the specific growth rate and efficiency of feed, but does not affect conversion of feed and survival rate (SR). The addition of flour E. spinosum feed up to a dose of 4% can give an increase in absolute weight 4.79 g, absolute length 2.38 cm, specific growth rate (SGR) 2.62%, efficiency of feed 66.54% and feed conversion ratio (FCR) 1.47.Keywords: Eucheuma spinosum; Feed; Fish carp